Xylella phage MATE 2: a novel bacteriophage with potent lytic activity against Xylella fastidiosa subsp. pauca - Sabri, Miloud; El Handi, Kaoutar; Cara, Orges; De Stradis, Angelo; Valentini, Franco; Elbeaino, Toufic (Frontiers in Microbiology, 2024)
Xylella fastidiosa (Xf) is a major phytosanitary threat to global agricultural production. The complexity and difficulty of controlling Xf underscore the pressing need for novel antibacterial agents, i.e., bacteriophages, which are natural predators of bacteria. In this study, a novel lytic bacteriophage of Xf subsp. pauca, namely Xylella phage MATE 2 (MATE 2), was isolated from sewage water in southern Italy. Biological characterization showed that MATE 2 possessed a broad-spectrum of antibacterial activity against various phytobacteria within the family Xanthomonadaceae, a rapid adsorption time (10 min), and high resistance to a broad range of pH (4-10) and temperatures (4-60 °C). Most importantly, MATE 2 was able to suppress the growth of Xf subsp. pauca cells in liquid culture for 7 days, demonstrating its potential as an effective antibacterial agent against Xf. The genomic and electron microscopy analyses revealed that MATE 2 is a new species tentatively belonging to the genus Carpasinavirus within the class Caudoviricetes, with an isometric capsid head of 60 ± 5 nm along with a contractile tail of 120 ± 7.5 nm. Furthermore, the high-throughput sequencing and de novo assembly generated a single contig of 63,695 nucleotides in length; representing a complete genome composed of 95 Open Reading Frames. Bioinformatics analysis performed on MATE 2 genome revealed the absence of lysogenic mediated genes, and genes encoding virulence factors, antibiotic resistance, and toxins.This study adds a new phage to the very short list of Xf-infecting lytic phages, whose in-vitro antibacterial activity has been ascertained, while its efficacy on Xf-infected olive trees in the field has yet to be determined.